2013
DOI: 10.1080/09602011.2012.747443
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and initial efficacy of a cognitive-behavioural group programme for managing anger and aggressiveness after traumatic brain injury

Abstract: This study assesses the feasibility of a cognitive-behavioural group programme for treating anger and aggressiveness after a traumatic brain injury (TBI). Five feasibility criteria were considered: demand, implementation, practicality, acceptability and initial efficacy. A self-report questionnaire of aggressiveness (AQ-12) was administered before the intervention (T1), one week following the intervention (T2) and at a four months follow-up (T3). Ten patients with moderate to severe chronic TBI completed the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Furthermore, the frequency and intensity of neuropsychiatric symptoms such as aggressiveness, hallucinations and delusions tend to increase at sunset (an effect termed the 'sundown syndrome') and are often correlated with caregiver's burden (Allegri et al, 2006;Khachiyants, Trinkle, Son, & Kim, 2011). CBT reduces anger and aggressiveness in patients with brain injury (Aboulafia-Brakha, Greber Buschbeck, Rochat, & Annoni, 2013), and the frequency of these symptoms also decreases in AD patients following psychosocial interventions for their caregivers (Stella et al, 2011). In line with this finding, in the current study caregivers reported a significant reduction of neuropsychiatric symptoms of their AD relatives, with a large effect size and high statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the frequency and intensity of neuropsychiatric symptoms such as aggressiveness, hallucinations and delusions tend to increase at sunset (an effect termed the 'sundown syndrome') and are often correlated with caregiver's burden (Allegri et al, 2006;Khachiyants, Trinkle, Son, & Kim, 2011). CBT reduces anger and aggressiveness in patients with brain injury (Aboulafia-Brakha, Greber Buschbeck, Rochat, & Annoni, 2013), and the frequency of these symptoms also decreases in AD patients following psychosocial interventions for their caregivers (Stella et al, 2011). In line with this finding, in the current study caregivers reported a significant reduction of neuropsychiatric symptoms of their AD relatives, with a large effect size and high statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…The AQ-12 shows acceptable levels of internal consistency and good test-re-test reliability (Cronbach's alpha coefficient of 0.80 for the French version). This same questionnaire was used in a previous study with TBI participants [9].…”
Section: Main Outcome Measuresmentioning
confidence: 97%
“…This 8-week programme with 60-minute sessions held oncea-week is described in a previous study assessing its feasibility and initial efficacy carried-out with 11 patients [9]. The protocol is composed of four main modules and covers (1) Identification of emotions/self-awareness; (2) Managing emotion in emergency situations (relaxation techniques, behaviour interruption); (3) Cognitive restructuring; and (4) Prevention strategies such as identifying vulnerable situations and promoting pleasant activities.…”
Section: Anger Management Programme (A)mentioning
confidence: 99%
See 2 more Smart Citations